Doped modified NCM ternary positive electrode material and preparation method thereof
Patent Information
- Application Number
- CN202611103441.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]本发明的目的在于提供一种掺杂改性的NCM三元正极材料,以解决现有技术中NCM三元正极材料在高容量和高倍率性能下其循环性能弱,会产生阳离子混排和晶格不稳定的现象
1.本发明通过采用氧化锆与氧化钇协同掺杂并结合分段烧结工艺,对NCM三元正极材料进行改性,显著提升了其结构稳定性与电化学性能。锆的引入可在晶格中形成强ZrO键,有效增强晶体结构的机械强度,抑制循环过程中因体积变化引起的微裂纹产生,从而改善锂离子传输路径的完整性;同时,锆元素掺杂有助于稳定晶格氧,缓解高电压下的氧释放问题。钇的掺杂则进一步发挥稳定作用,Y3+离子可进入晶格并优先占据锂层附近位置,通过静电排斥效应抑制Ni2+向锂层的迁移,显著降低阳离子混排程度,维持层状结构的规整性。两种掺杂元素的协同作用,不仅在体相中强化了晶体框架,也在近表面区域形成稳定界面,共同提升材料在高电压和高镍条件下的结构耐受性。
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion batteries, and in particular to a doped and modified NCM ternary cathode material and its preparation method. Background Technology
[0002] In recent years, with the rapid development of 3C electronic products, new energy electric vehicles, energy storage, and communications, the application space of lithium-ion batteries has become increasingly broad. As a crucial component of batteries, cathode materials have a significant impact on the performance and cost of lithium-ion batteries. Developing high-performance, low-cost cathode materials is essential and will effectively promote the further development and widespread application of lithium-ion batteries. Ternary nickel-cobalt-manganese cathode materials are a relatively new type of cathode material. Their cost and cobalt usage are far lower than traditional lithium cobalt oxide cathode materials, while their energy density is higher than the popular lithium iron phosphate materials. Due to their advantages such as low cost, environmental friendliness, high capacity, and good cycle performance, the research and improvement of ternary cathode materials has always been a research hotspot in the battery field, driven by the pursuit of higher-performance batteries.
[0003] However, ternary materials also have some problems in application. Increasing the nickel content and charging cutoff voltage to improve energy density will significantly reduce the lifespan and safety of the cathode material. Insufficient thermal stability and cycle stability mean that safety and lifespan cannot meet the requirements of power batteries. (The last sentence appears to be incomplete and possibly refers to a different topic.) + and Ni 2+ With similar ionic radii, Li... + and Ni 2+ Ni tends to exchange positions within a single-crystal lattice, leading to cation disorder or mixing. When Ni occupies interlayer positions in the lattice... 2+ When oxidized, the significant change in ionic radius leads to distortion of the Li layer structure, causing lattice collapse and blocking lithium diffusion pathways. 2+ Migration can also lead to phase transitions, disrupt the layered structure of materials, and affect their electrochemical performance.
[0004] Therefore, there is an urgent need for a material that can solve the problems of ternary nickel-cobalt-manganese materials, give full play to the advantages of this material, and improve its cycle performance, cation mixing and lattice stability while maintaining high capacity and good rate performance. Summary of the Invention
[0005] The purpose of this invention is to provide a doped and modified NCM ternary cathode material to solve the problems of weak cycle performance, cation mixing and lattice instability in existing NCM ternary cathode materials under high capacity and high rate performance.
[0006] The present invention also aims to provide a method for preparing doped and modified NCM ternary cathode materials, which can be used to prepare cathode materials with high capacity, high rate capability, and good cycle stability.
[0007] In a first aspect, the present invention discloses a method for preparing a doped and modified NCM ternary cathode material, comprising the following steps: S1. The lithium source, nickel-cobalt-manganese hydroxide precursor, yttrium-containing compound and zirconium-containing compound are ball-milled to obtain a mixture. S2. The mixture is sintered in stages, first pre-fired at low temperature, then sintered at high temperature, cooled to room temperature, and then crushed and sieved to obtain the final product.
[0008] By employing the above technical solutions, uniform doping and lattice fusion of yttrium and zirconium-containing elements in NCM ternary cathode materials were achieved, improving the crystal structure and surface chemical properties of the material through their synergistic effect. Step S1, through ball milling with specific parameters, ensures sufficient contact and uniform mixing of the lithium source, precursor, and dopant compound, avoiding performance fluctuations caused by uneven local doping concentrations. This lays the foundation for sufficient reaction of each component and uniform diffusion of dopant elements during subsequent sintering. Step S2, a segmented sintering process, removes impurities and moisture from the raw materials through low-temperature pre-sintering, creating a clean environment for lattice growth at high temperatures. High-temperature main sintering then promotes the complete formation of the layered crystal structure and achieves effective embedding of dopant elements into the lattice. Specifically, the introduction of zirconium forms strong Zr-O bonds in the lattice, effectively enhancing the mechanical strength of the crystal structure and suppressing microcracks caused by volume changes during cycling, thereby improving the integrity of the lithium-ion transport path. Simultaneously, zirconium doping helps stabilize lattice oxygen, alleviating oxygen release problems under high voltage. Yttrium doping further plays a stabilizing role, Y... 3+ Ions can enter the crystal lattice and preferentially occupy positions near the lithium layer, suppressing Ni through electrostatic repulsion. 2+ Migration to the lithium layer significantly reduces cation mixing and maintains the regularity of the layered structure. The synergistic effect of the two dopants not only strengthens the crystal framework in the bulk phase but also forms a stable interface in the near-surface region, jointly improving the structural tolerance of the material under high voltage and high nickel conditions, ultimately resulting in a cathode material with excellent overall performance.
[0009] Preferably, in step S1, the yttrium-containing compound includes yttrium oxide and yttrium nitrate; the doping amount of the yttrium-containing compound is 300 to 800 ppm based on the element Y.
[0010] Preferably, the zirconium-containing compound includes zirconium oxide and zirconium nitrate; the doping amount of the zirconium-containing compound is 1500 to 25000 ppm based on Zr element.
[0011] Preferably, the lithium source includes one or more of lithium hydroxide, lithium carbonate, lithium nitrate, or lithium acetate.
[0012] Preferably, the chemical formula of the nickel-cobalt-manganese hydroxide precursor is [Ni 1-x-y Co x Mn y ](OH)2, where 0≤x≤0.1, 0≤y≤0.1.
[0013] Preferably, in step S1, the ball milling speed is 200-400 r / min and the ball milling time is 3-6 h.
[0014] Preferably, in step S2, the temperature of the low-temperature preheating is 600-700℃, and the holding time is 2-4 hours.
[0015] Preferably, in step S2, the temperature of the high-temperature main firing is 940-970℃, the holding time is 10-14h, and the heating rate is 2-3℃ / min.
[0016] Preferably, in step S2, the segmented sintering is carried out in an oxygen or air atmosphere.
[0017] On the other hand, the present invention also provides a doped and modified NCM ternary cathode material.
[0018] The beneficial effects of this invention are: 1. This invention modifies NCM ternary cathode materials by employing synergistic doping of zirconium oxide and yttrium oxide combined with a segmented sintering process, significantly improving their structural stability and electrochemical performance. The introduction of zirconium can form a strong Zr group in the crystal lattice. O bonds effectively enhance the mechanical strength of the crystal structure and suppress the formation of microcracks caused by volume changes during cycling, thereby improving the integrity of the lithium-ion transport path. Simultaneously, zirconium doping helps stabilize lattice oxygen, mitigating oxygen release issues under high voltage. Yttrium doping further enhances this stabilizing effect. 3+ Ions can enter the crystal lattice and preferentially occupy positions near the lithium layer, suppressing Ni through electrostatic repulsion. 2+ Migration to the lithium layer significantly reduces cation mixing and maintains the regularity of the layered structure. The synergistic effect of the two dopants not only strengthens the crystal framework in the bulk phase but also forms a stable interface in the near-surface region, jointly improving the structural tolerance of the material under high voltage and high nickel conditions.
[0019] 2. The segmented sintering process employed in this invention involves first pre-sintering at a low temperature to allow for the initial diffusion of dopant elements and promote a uniform reaction between the lithium source and the precursor, followed by high-temperature main sintering to complete grain growth and structural densification. This process helps achieve uniform distribution of dopant elements and optimized control of grain size, avoiding lithium volatilization and exacerbation of lattice defects caused by single high-temperature sintering. This preparation method is simple, uses readily available raw materials, and is easy to scale up for production. The resulting cathode material maintains high specific capacity while exhibiting excellent cycle stability, rate performance, and thermal safety, making it suitable for high-energy-density lithium-ion battery systems. Detailed Implementation
[0020] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below.
[0021] A method for preparing a doped and modified NCM ternary cathode material includes the following steps: S1. The lithium source, nickel-cobalt-manganese hydroxide precursor, yttrium-containing compound and zirconium-containing compound are ball-milled to obtain a mixture. S2. The mixture is sintered in stages, first pre-fired at low temperature, then sintered at high temperature, cooled to room temperature, and then crushed and sieved to obtain the final product.
[0022] By employing the above technical solutions, uniform doping and lattice fusion of yttrium and zirconium-containing elements in NCM ternary cathode materials were achieved, improving the crystal structure and surface chemical properties of the material through their synergistic effect. Step S1, through ball milling with specific parameters, ensures sufficient contact and uniform mixing of the lithium source, precursor, and dopant compound, avoiding performance fluctuations caused by uneven local doping concentrations. This lays the foundation for sufficient reaction of each component and uniform diffusion of dopant elements during subsequent sintering. Step S2, a segmented sintering process, removes impurities and moisture from the raw materials through low-temperature pre-sintering, creating a clean environment for lattice growth at high temperatures. High-temperature main sintering then promotes the complete formation of the layered crystal structure and achieves effective embedding of dopant elements into the lattice. Specifically, the introduction of zirconium forms strong Zr-O bonds in the lattice, effectively enhancing the mechanical strength of the crystal structure and suppressing microcracks caused by volume changes during cycling, thereby improving the integrity of the lithium-ion transport path. Simultaneously, zirconium doping helps stabilize lattice oxygen, alleviating oxygen release problems under high voltage. Yttrium doping further plays a stabilizing role, Y... 3+ Ions can enter the crystal lattice and preferentially occupy positions near the lithium layer, suppressing Ni through electrostatic repulsion. 2+Migration to the lithium layer significantly reduces cation mixing and maintains the regularity of the layered structure. The synergistic effect of the two dopants not only strengthens the crystal framework in the bulk phase but also forms a stable interface in the near-surface region, jointly improving the structural tolerance of the material under high voltage and high nickel conditions, ultimately resulting in a cathode material with excellent overall performance.
[0023] In some embodiments, in step S1, the yttrium-containing compound includes yttrium oxide and yttrium nitrate; the doping amount of the yttrium-containing compound, calculated as Y element, is 300–800 ppm; this doping range can precisely control the surface and bulk structure of the material, effectively suppressing Ni. 2+ The migration to the Li layer reduces cation mixing and enhances the binding force between oxygen and metal ions, thereby improving the structural stability of the material. If the doping concentration is below 300 ppm, the modification effect is insufficient, while concentrations above 800 ppm can easily lead to lattice distortion and affect lithium-ion transport efficiency.
[0024] In some embodiments, the zirconium-containing compound includes zirconium oxide and zirconium nitrate; the doping amount of the zirconium-containing compound is 1500 to 25000 ppm based on Zr element; this doping range can enhance the lattice structure strength through strong Zr-O bonds, improve atomic stability, and suppress the generation of microcracks during cycling. If the doping amount is too low, the lattice stabilization effect is limited, and if it is too high, it can easily lead to disordered arrangement of transition metal layers and reduce the electrochemical activity of the material.
[0025] In some embodiments, the lithium source includes one or more of lithium hydroxide, lithium carbonate, lithium nitrate, or lithium acetate; preferably lithium carbonate or lithium hydroxide, which has a stable lithium content, a decomposition temperature that is compatible with the sintering process, can ensure a sufficient supply of lithium ions, reduce Li / Ni mixing, and improve the discharge specific capacity of the material.
[0026] In some embodiments, the chemical formula of the nickel-cobalt-manganese hydroxide precursor is [Ni 1-x-y Co x Mn y [(OH)2, where 0≤x≤0.1, 0≤y≤0.1; the low cobalt and high nickel composition design corresponding to this chemical formula can reduce production costs while ensuring high energy density of the material. The range of values for x and y can be adjusted according to actual performance requirements, taking into account both capacity and stability.
[0027] In some embodiments, in step S1, the ball milling speed is 200-400 r / min and the ball milling time is 3-6 h. This parameter range can achieve uniform mixing of raw materials, avoid uneven doping caused by insufficient ball milling or agglomeration of raw material particles caused by excessive ball milling, and ensure that the reaction of each component is sufficient in the subsequent sintering process.
[0028] In some embodiments, in step S2, the temperature of the low-temperature pre-firing is 600-700°C and the holding time is 2-4 hours. This combination of temperature and holding time can gently remove adsorbed water and crystal water from the raw materials, avoid material agglomeration caused by rapid heating, and create favorable conditions for lattice growth in the high-temperature main firing stage.
[0029] In some embodiments, in step S2, the high-temperature sintering temperature is 940–970°C, the holding time is 10–14 h, and the heating rate is 2–3°C / min. These process parameters can promote the complete formation of the layered crystal structure, the precise control of the heating rate can reduce lattice defects caused by thermal stress, and the holding time ensures that the doped elements fully diffuse into the lattice, thereby improving the cycle stability and discharge performance of the material.
[0030] In some embodiments, in step S2, segmented sintering is carried out in an oxygen or air atmosphere; an oxygen atmosphere can further suppress the release of lattice oxygen and improve the thermal stability of the material, while an air atmosphere is more suitable for industrial production and reduces process costs. Both atmospheres can meet the sintering requirements of the material.
[0031] The specific embodiments of the present invention will be described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments.
[0032] Example Example 1: A doped and modified NCM ternary cathode material was prepared by the following method: S1. Lithium hydroxide, nickel cobalt manganese hydroxide precursor [Ni 0.92 Co 0.06 Mn 0.02 (OH)2, zirconium oxide, and yttrium oxide are placed in a ball mill jar in a certain ratio and milled at 300 r / min for 5 hours to obtain a uniform mixture. The ratio of lithium hydroxide and nickel cobalt manganese hydroxide precursor is 1:1 with a Li to Mn molar ratio of 1:1. The doping amount of zirconium oxide is 2000 ppm and the doping amount of yttrium oxide is 500 ppm. S2. After the mixture is placed in a bowl, it is pre-sintered at a low temperature of 600℃ for 3 hours in an air atmosphere, and then sintered at a high temperature of 950℃ for 12 hours. The sintering heating rate is 3℃ / min. After natural cooling to room temperature, the zirconium oxide and yttrium oxide doped lithium nickel cobalt manganese oxide ternary cathode material is obtained after crushing and sieving.
[0033] Example 2: A doped and modified NCM ternary cathode material was prepared by the following method: S1. Lithium hydroxide, nickel cobalt manganese hydroxide precursor [Ni 0.92 Co 0.06 Mn 0.02(OH)2, zirconium oxide, and yttrium oxide are placed in a ball mill jar in a certain ratio and milled at 300 r / min for 5 hours to obtain a uniform mixture. The ratio of lithium hydroxide and nickel cobalt manganese hydroxide precursor is 1:1 with a Li to Mn molar ratio of 1:1. The doping amount of zirconium oxide is 1500 ppm and the doping amount of yttrium oxide is 300 ppm. S2. After the mixture is placed in a bowl, it is pre-sintered at a low temperature of 600℃ for 3 hours in an air atmosphere, and then sintered at a high temperature of 950℃ for 12 hours. The sintering heating rate is 3℃ / min. After natural cooling to room temperature, the zirconium oxide and yttrium oxide doped lithium nickel cobalt manganese oxide ternary cathode material is obtained after crushing and sieving.
[0034] Example 3: A doped and modified NCM ternary cathode material was prepared by the following method: S1. Lithium hydroxide, nickel cobalt manganese hydroxide precursor [Ni 0.92 Co 0.06 Mn 0.02 (OH)2, zirconium oxide, and yttrium oxide are placed in a ball mill jar in a certain ratio and milled at 300 r / min for 5 hours to obtain a uniform mixture. The ratio of lithium hydroxide and nickel cobalt manganese hydroxide precursor is 1:1 with a Li to Mn molar ratio of 1:1. The doping amount of zirconium oxide is 2500 ppm and the doping amount of yttrium oxide is 800 ppm. S2. After the mixture is placed in a bowl, it is pre-sintered at a low temperature of 600℃ for 3 hours in an air atmosphere, and then sintered at a high temperature of 950℃ for 12 hours. The sintering heating rate is 3℃ / min. After natural cooling to room temperature, the zirconium oxide and yttrium oxide doped lithium nickel cobalt manganese oxide ternary cathode material is obtained after crushing and sieving.
[0035] Comparative Example Comparative Example 1 is a doped and modified NCM ternary cathode material, which differs from Example 1 only in that the doping amount of yttrium oxide is 200 ppm.
[0036] Comparative Example 2 is a doped and modified NCM ternary cathode material, which differs from Example 1 only in that yttrium oxide is not added.
[0037] Comparative Example 3 is a doped and modified NCM ternary cathode material, which differs from Example 1 only in that zirconium oxide is not added.
[0038] Comparative Example 4: A doped and modified NCM ternary cathode material, which differs from Example 1 only in that the high-temperature sintering temperature is 900°C.
[0039] Performance testing: The doped and modified NCM ternary cathode materials prepared in Examples 1-3 and Comparative Examples 1-4 were fabricated into cathode sheets using conventional methods, and then combined with lithium anode sheets to form button cells for the following performance tests: 1. Charging capacity test: The battery is charged from 3.0V to 4.3V at a charging rate of 0.1C in an environment of 25℃, and then discharged to 3.0V at a discharging rate of 0.1C. The 0.1C charging capacity is measured.
[0040] 2. Cycle capacity retention test: The battery was charged from 3.0V to 4.3V at a charging rate of 0.5C in an environment of 45℃, and then discharged to 3.0V at the same rate. The discharge capacity of this discharge was determined as the initial discharge capacity. The discharge capacity of the 20th discharge was measured after 20 charge-discharge cycles. The cycle retention rate is the ratio of the 20th discharge capacity to the initial discharge capacity. The results of the performance test are shown in Table 1.
[0041] Table 1 Performance test results
[0042] As shown in Table 1, Examples 1 to 3 of this invention, using 1500-2500 ppm zirconium oxide and 300-800 ppm yttrium oxide co-doping combined with a segmented sintering process, produced cathode materials exhibiting high charging capacities (>248 mAh / g) and excellent capacity retention (>95.8%). In contrast, Comparative Example 2 (undoped yttrium) and Comparative Example 3 (undoped zirconium) showed significantly reduced capacity retention, confirming that the synergistic doping of Zr and Y plays a crucial role in suppressing cation mixing and stabilizing the crystal structure; neither is dispensable. Comparative Example 1, with less than 200 ppm yttrium doping, also showed significant performance degradation, indicating that the doping range determined in this invention is the optimized range for achieving the best synergistic effect. Comparative Example 4, with a sintering temperature of 900℃, showed acceptable capacity retention, but a decrease in charging capacity, indicating that high-temperature sintering at 940-970℃ is crucial for forming a complete layered structure and ensuring high capacity. The above data fully demonstrates that the present invention achieves a balance between high capacity and high cycle stability through specific element synergy, precise doping ratios, and optimized sintering processes.
[0043] The above-disclosed embodiments are merely a few specific examples of the present invention. However, the embodiments of the present invention are not limited thereto, and any variations that can be conceived by those skilled in the art should fall within the protection scope of the present invention.
Claims
1. A method for preparing a doped and modified NCM ternary cathode material, characterized in that, Includes the following steps: S1. The lithium source, nickel-cobalt-manganese hydroxide precursor, yttrium-containing compound and zirconium-containing compound are ball-milled to obtain a mixture. S2. The mixture is sintered in stages, first pre-fired at low temperature, then sintered at high temperature, cooled to room temperature, and then crushed and sieved to obtain the final product.
2. The method for preparing the doped and modified NCM ternary cathode material according to claim 1, characterized in that, In step S1, the doping amount of the yttrium-containing compound is 300-800 ppm based on the element Y; the yttrium-containing compound includes yttrium oxide and yttrium nitrate.
3. The method for preparing the doped and modified NCM ternary cathode material according to claim 2, characterized in that, The doping amount of the zirconium-containing compound is 1500-25000 ppm based on Zr element; the zirconium-containing compound includes zirconium oxide and zirconium nitrate.
4. The method for preparing the doped and modified NCM ternary cathode material according to claim 1, characterized in that, The lithium source includes one or more of lithium hydroxide, lithium carbonate, lithium nitrate, or lithium acetate.
5. The method for preparing the doped and modified NCM ternary cathode material according to claim 1, characterized in that, The chemical formula of the nickel-cobalt-manganese hydroxide precursor is [Ni 1-x-y Co x Mn y ](OH)2, where 0≤x≤0.1, 0≤y≤0.
1.
6. The method for preparing the doped and modified NCM ternary cathode material according to claim 1, characterized in that, In step S1, the ball milling speed is 200-400 r / min, and the ball milling time is 3-6 h.
7. The method for preparing the doped and modified NCM ternary cathode material according to claim 1, characterized in that, In step S2, the temperature of the low-temperature preheating is 600-700℃, and the holding time is 2-4 hours.
8. The method for preparing the doped and modified NCM ternary cathode material according to claim 1, characterized in that, In step S2, the temperature of the high-temperature main firing is 940-970℃, the holding time is 10-14h, and the heating rate is 2-3℃ / min.
9. The method for preparing the doped and modified NCM ternary cathode material according to claim 1, characterized in that, In step S2, the segmented sintering is carried out in an oxygen or air atmosphere.
10. A doped and modified NCM ternary cathode material, characterized in that, The doped and modified NCM ternary cathode material is prepared by the preparation method described in any one of claims 1-9.